ANALISIS IMPLEMENTASI UNDANG-UNDANG NOMOR 7 TAHUN 2017 TENTANG PEMILIHAN UMUM TERHADAP PROBLEMATIKA SISTEM PELAKSANAAN PEMILIHAN UMUM DI INDONESIA - Zendrato , Iman Sejati; Br. Sembiring, Tamaulina; Tambunan , Zakaria; Azlina, Wida; Suparman, Muhammad Arif; Suwirza , Eka; Meilani , Widya; Pohan , Majidah; Manik , Dibi Vation; Harita , Amos (Gapenas Publisher, 2025)
As a democratic country, Indonesia relies on elections as the main means of realizing people's sovereignty. The application of general elections as the main pillar of democracy is expected to be a vehicle for people's sovereignty that is carried out directly, publicly, freely, secretly, honestly, and fairly. However, in its implementation, it is still overshadowed by structural complexity and multidimensional challenges as a problem, such as geographical disparities, socio-economic inequality, low political literacy, and limited institutional capacity of general election organizers such as the General Election Commission (KPU), the Election Supervisory Agency (Bawaslu), and the Honorary Council of Election Organizers (DKPP). The research uses a normative juridical approach with a qualitative-descriptive method. The results of the analysis show that although the General Election Law has provided a fairly complete legal framework, its implementation has not been able to guarantee a completely honest, fair and democratic election. Systemic reforms are needed through institutional strengthening, political education, and the use of information technology so that elections in Indonesia can be carried out in an inclusive, transparent, and integrity manner as a reflection of the will of the sovereign people.